The factors influence job satisfaction among employee at Hijrah Water Sdn. Bhd. / Muhamad Syafiq Hamzi Mohamad - Mohamad, Muhamad Syafiq Hamzi (Faculty of Business and Management, 2014)
In order to gain competitive advantage that enable the organization different from their competitor, the organization must also have their own talented and valued employee that will bring benefits to the company. The organization must recruit the talented employees in order to achieve the competitive advantage. However, the talented employees are not exactly loves their job or task given. As for Hijrah Water Sdn Bhd, the researcher attracted to identify what are the determinants that make the employees satisfied with their job in that organization. Even though the organization is a medium organization, but the employees are loyal to the organization. The first research objective is to identify the relationship between working condition and the job satisfaction. Second objectives are to identify the relationship between leadership and the job satisfaction of the employee. Third objectives are to identify the relationship between pay/salary and job satisfaction of the employee. The last objective is to identify most influence factor in job satisfaction. The total respondents are 40 respondents which are the population of respondent is the similar number with sampling. The data were collected through distribution of questionnaire survey and interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation. The findings supported all four (4) objectives which mean there is no relationship between all three (3) independent variables which are working condition, leadership and pay/salary with the dependent variable, job satisfaction gaining for Hijrah Water Sdn Bhd.